Nuclear entrapment of p33ING1b by inhibition of exportin-1: A trigger of apoptosis in head and neck squamous cell cancer - í–zdaş, Sibel (Cellular and Molecular Biology, 2018)
The effect of deregulation of nuclear export mediated by exportin-1, with consequent cellular mislocalization of p33ING1b, a member of the tumor suppressor gene family, has not been previously investigated in head and neck squamous cell cancer (HNSCC). We evaluated the effect of reversing cytoplasmic p33ING1b localization through inhibition of exportin-1 by leptomycin B (LMB) and the effect of nuclear entrapment of p33ING1b on molecular alterations in primary and metastatic HNSCC lines. The expression and location of exportin-1 and p33ING1b were analyzed by a quantitative real"‘time reverse transcription polymerase chain reaction PCR (qRT-PCR), a Western blot, and immunostaining. Cell proliferation and migration assays were conducted to determine the effect of exportin-1 inhibition on the cell lines. Exportin-1 was overexpressed in metastatic HNSCC, whereas p33ING1b was poorly expressed. Exportin-1 inhibition induced nuclear entrapment and upregulation of p33ING1b, extensive apoptosis, and growth arrest. It also suppressed cell migration. Cytoplasmic p33ING1b-mediated regulation of cell growth and nuclear entrapment of p33ING1b via inhibition of exportin-1 may be a key mechanism for inducing HNSCC apoptosis.